Characteristics of the public (state) supervision of reinsurance activities - Войцеховська, Ірина Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article examines the characteristics of the public (state) supervision of reinsurance activities in Ukraine, analyzes the contemporary experience of EU member states in the relevant sphere and grounds the necessity of separating public (state) supervision system of reinsurance activities from the public oversight of the insurance business. Actuality of this paper is caused by the lack of a separate system of public supervision of reinsurance activities in Ukraine as one of the main conditions for the effective exercise of an economic activity. The objectives of the article are to analyze the current state of public supervision of reinsurance activities in Ukraine, identify significant disadvantages of its carrying out and justify based on the European experience expediency delimitation of public supervision of reinsurance activities from state supervision of insurance activities. The article analyzes the features of the models of state supervision of professional reinsurers that have been formed in the world. However, the author concludes that such models of state supervision are practically do not find their reflection in practice in most European countries, which is primarily due to the awareness of need for a particular type of state supervision of reinsurance activities and to the process of unification of approaches to its carrying out internationally. The author also points out that with the international acts in this field (in particular Directive 2005/68/EC of the European Parliament and of the Council of 16 November 2005 on reinsurance and amending Council Directives 73/239/EEC, 92/49/EEC as well as Directives 98/78/EC and 2002/83/EC) has been achieved the following results: the introduction of mandatory state supervision of reinsurance activities; delimitation of state supervision of reinsurance activities from supervision of insurance activities; the establishment of common principles of state supervision which in turn has created an opportunity to guarantee uniform system of supervision, valid throughout the European Community. The article also analyzes the current state of public supervision of reinsurance activities in Ukraine and concludes that in this country is typical state supervision model in which its effecting is similar to the state supervision of insurance activities. The author does not agree with the current legislative approach and argues the need to introduce a separate system of supervision of reinsurance activities based on analyzing some of its destinations. As a result the author concludes that today in Ukraine the state supervision of reinsurance activities takes place through a system of supervision of insurance activities. This position of the national legislature the author finds unjustified and suggests reforming and modernizing the legislation of Ukraine in this area.